Answer:
(x-4) is not a factor of f(x)=x³-2x²+5x+1
Step-by-step explanation:
Uding the remainder theorem,(x-4) is a factor if the remainder is 0
Plug in x=4
(4)³-2(4)²+5(4)+1
64-32+20+1
64-53
11
Answer:
Step-by-step explanation:
It’s d
5^5-9(200/4)-(10*90)/5-4^4(5)+156-256
= 3125-9( 200/4)-(10*90)/5-(4^4)(5)+156-256
= 3125-(9)(50)- (10*90)/5-(4^4)(5)+156-256
= 3125-450- (10*90)/5-(4^4)(5)+156-256
= 2675-(10*90)/5-(4^4)(5)+156-256
= 2675 - 900/5 - (4^4)(5)+156-256
= 2675 - 180 - (4^4)(5)+156-256
= 2495 - (4^4)(5)+156-256
= 2495 - 1280 + 156 -256
= 1215 + 156 - 256
= 1371 - 256
= 1115
I hope that's help , please if you have question(s) just let me know !
Answer:
A.
Step-by-step explanation: